Textile technique in jewellery making – ‘Soumak’ technique / Rozita Shamsuddin - Shamsuddin, Rozita (UiTM Perak Press, 2022)
Textile techniques are traditionally worked with fibres such as linen, cotton, and silk. However, they can also be applied to metal. There has been a recent increase in jewelers using textile techniques in their work, and many books provide a thorough and comprehensive introduction to all the materials and techniques to start in this exciting area of jewelry making. This crossover adaptability is especially evident with metals in the creation of jewelry and adornment. These methods provide an aesthetically rich yet simple way for a jewelry maker to engage with the material. Weaving is the interlacing together of two distinct and separate sets or ‘sheets’ of threads. Weaving is the interlacing of two sets of elements, one vertical and one horizontal. The two sets of threads lie at right angles to each other. One set is called the warp, and the other set, the horizontal, is called the weft. The two interlaced together to form the structure. In metal application, the vertical element – the warp – is a sheet that is cut into strips or wedges. The horizontal element – the weft – is multiple strands of thin wire twisted together. The pattern is a Plain Weave, in which the wire crosses over the sheet, then under the sheet, continuing over one warp, under one warp. Soumak is one of the weaving techniques in Textile. Soumak is a tapestry technique of weaving sturdy, decorative fabrics used for rugs, domestic bags, and bedding, with soumak fabrics used for bedding known as soumak mafrash. This technique involves wrapping colored weft threads over and under the warp threads, allowing you to work on vertical, horizontal, or diagonal sections at any one time. The beauty of soumak technique in jewelry making sophisticated, unusual, and endlessly appealing.